(untitled) (Indo-MathEdu Intellectuals Journal, 2023)
This study was motivated by the lack of self-confidence, fear, worry, discomfort, and nervousness of students during the mathematics learning process and the low mathematical communication skills of students. This study aims to determine the effect of self-efficacy and mathematical anxiety on students’ mathematical communication skills. This type of research is correlational research with quantitative methods. The research instrumental used are self-efficacy questionnaire, mathematical anxiety questionnaire and mathematical communication ability test. The population in this study amounted to 43 people with a sample size of 39 people taken using probability sampling with simple random sampling technique. The data analysis used is multiple linear regression. Based on the results of the study, obtained in the First hypothesis the value of tcount(3.9116) >ttabel (0.0631) with H0 rejected and Ha accepted which if students’ self-efficacy is higher then students’ mathematical communication skills are also higher and vice versa. In the second hypothesis, the value of tcount(0.2819)>ttabel (0.0631), with H0 rejected and Ha accepted which if students’ math anxiety is high then their math communication skills are low and vice versa. Concluded that the two independent variables together have a significant influence on the dependent variable with a percentage of 32.45%.